Application of titanium regulates the functional components of photosynthetic apparatus in grafted seedlings of Carya cathayensis Sarg. under shade. (March 2022) - Yan, Daoliang; Song, Feng; Li, Zhen; Sharma, Anket; Xie, Xiaoting; Wu, Tingting; Wang, Xiaofei; He, Yi; Chen, Jiabao; Huang, Qiaoyu; Zhao, Lu; Wu, Rongling; et al.
Abstract: Light acts as a key environmental factor for normal growth and development of plants. Carya cathayensis Sarg. (hickory) faces low light conditions, especially those caused by cloudy or rainy days during the rapid growth period, which has caused adverse effects on its growth. In the current investigation, to alleviate the adverse effects of insufficient light on the cultivation of hickory, anti-hydrolyze stabilized ionic titanium (ASIT) was sprayed on the leaves of the three kinds of grafted seedlings and the non-grafted seedlings of hickory grown under different shade conditions. Results showed that the leaf mass per area and chlorophyll content of grafted hickory seedlings were increased after ASIT application. Rubisco content and photosynthetic rate ( P n ) of seedlings grown under shading conditions were positively affected by ASIT treatment, especially on the 45th day of treatment, while the interaction effects of the two parameters between ASIT application and different shade treatments were significant. Titanium accumulation was the highest in roots, followed by leaves, and then in stems, while ASIT had the most significant effects on roots and leaves under 50 ± 5% shade. Severe shading inhibited growth and lead to serious destruction of chloroplast ultrastructure. In addition, the role of ASIT was rootstock-dependent, since ASIT had the weakest mitigation effect on the C/H grafted seedlings. To sum up, the application of ASIT to the grafted seedlings of hickory could improve its ability to resist shade stress. Graphical abstract: Image 1 Highlights: Reduced photosynthesis of C. cathayensis seedlings under shade treatment. Enhanced photosynthesis of C. cathayensis seedlings by titanium under shade. Rootstock-specific photosynthetic changes of C. cathayensis seedlings.